Personalization services in art education environments: first survey results - Koukopoulos, Dimitrios; Dafiotis, Panagiotis; Sylaiou, Stella; Koukoulis, Konstantinos; Antoniou, Angeliki; Vital, Rebeka; Fidas, Christos (2022 13th International Conference on Information, Intelligence, Systems & Applications (IISA), 2022)
Personalization is the main vehicle in many learning environments for the provision of enhanced services to the end-users. This paper deals with the problem of providing personalization services in an art education environment. Specifically, we are interested in assisting art teachers to initiate an art exhibition for their students, art students to create virtual exhibitions and art exhibition visitors to have immersive and interactive experiences. The results discussed here are one of the first outputs of an EU-funded research project, namely CREAMS which aims to design, develop end evaluate a framework and open-source tools based on virtual, augmented, and mixed reality for the creation of virtual exhibitions for art students. Specifically, in this paper, we present a literature review concerning eXtended Reality (XR) technologies and personalization for art education purposes. Based on the findings of the literature review, along with expert opinions, we present a system design incorporating specific personalization services. In order to emphasize the strength of the proposed personalization services in the framework, we present a set of motivating scenarios.
Keywords: Art; Bibliographies; Education; Extended reality; Mixed reality; System analysis and design; X reality; art education; personalization; survey; virtual exhibitions